2020
DOI: 10.21203/rs.3.rs-29462/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between dietary patterns and prediabetes risk in a middle-aged Chinese population

Abstract: Background: Information regarding dietary patterns associated with prediabetes in the Chinese population is lacking. The objective of the present study was to explore the association between major dietary patterns and the risk of prediabetes in a middle-aged Chinese population. Methods: A total of 1761 participants (aged 45 to 59 years) were recruited in Hangzhou city, the capital of Zhejiang Province, China from June 2015 to December 2016. Dietary information was obtained by interview using a 138-item, valida… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 37 publications
0
13
1
Order By: Relevance
“…On the other hand, psychosocial stress appears to have a more important role in women rather than men [ 17 ]. However, the previous findings showed high-energy diet is related to a higher chance of prediabetes [ 18 , 19 ], our results were not shown this relationship and on the other hand, energy intake was lower among prediabetes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…On the other hand, psychosocial stress appears to have a more important role in women rather than men [ 17 ]. However, the previous findings showed high-energy diet is related to a higher chance of prediabetes [ 18 , 19 ], our results were not shown this relationship and on the other hand, energy intake was lower among prediabetes.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite inconsistencies in findings, most studies have shown that aging and abnormal biochemical, clinical, and anthropometric parameters including lipid profiles, liver enzymes, HTN, BMI, HC, WHR, WC) along with some socio-demographic characteristics and unhealthy lifestyle (income, education levels, gender, sleep habits, PA levels and etc.) increase the chances of prediabetes [ 4 , 15 , 18 , 22 – 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Southeastern China comprises many different provinces, but their diets all share the same regional characteristics. Rice was the main staple [6][7][8]. Its average intake per capita was 399.6 g/day.…”
Section: Dietary Patterns Of Han Population In Southeastern Chinamentioning
confidence: 99%
“…Data on physical activity was collected using the short form of International Physical Activity Questionnaire (IPAQ), and was expressed as metabolic equivalent hours per week(MET-h/week) [16]. Subsequently, physical activity level was categorized as light, moderate and heavy [24].Additional information including smoking(never, current, former smokers), education level(primary school or below, middle and high school, junior college or above) was collected with a written questionnaire. Current smokers were de ned as those who smoked at lease one cigarette per day.…”
Section: Assessment Of Other Variablesmentioning
confidence: 99%